Policy Matters! Wholistically Supporting Indigenous Students’ Journey to and Through Canadian Post-secondary Education - Tobin, Joe; Leveille, Andrea; Dunn, Donna; Ghag, Mindy; Pidgeon, Michelle (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2025)
Over the last 30 years, Canadian post-secondary institutions have been developing specific programs, supports, and services to support Indigenous student access to and persistence through post-secondary education. Part of the ongoing work of decolonization, reconciliation, and Indigenization is challenging a colonially imposed definition of success (e.g., GPA, degree completion within 4 years) to consider Indigenous students’ experiences and their success more wholistically. This project aimed to identify how Indigenous student success is supported by institutional policies, programs, and practices. The research process included conducting an Indigenous qualitative content analysis of 74 universities and 158 colleges (i.e., public, English, and French) websites along with six semi-structured interviews with various program providers. This article examines how Canadian post-secondary institutions can wholistically support Indigenous students’ educational journeys through effective policies, programs, and practices that enhance access, facilitate transitions, and foster persistence. The analysis found 47 access, 64 transition, and 50 persistence programs specifically for Indigenous students. The analysis also raised crucial questions related to program sustainability. Further research is needed to understand the impact of these initiatives on the persistence of the next seven generations.